2017
DOI: 10.1111/jgs.14801
|View full text |Cite
|
Sign up to set email alerts
|

Can Braden Score Predict Outcomes for Hospitalized Heart Failure Patients?

Abstract: Braden score is an independent predictor of mortality, LOS, and discharge destination among inpatients with HF. Further exploration of the use of Braden scores to identify inpatients who might benefit from specialized intervention is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 15 publications
0
19
0
1
Order By: Relevance
“…In addition to the variables we found to be independently associated with LOS, studies have also found independent relations between LOS and other variables as well. (21)(22)(23). However, limitations exist within these models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the variables we found to be independently associated with LOS, studies have also found independent relations between LOS and other variables as well. (21)(22)(23). However, limitations exist within these models.…”
Section: Discussionmentioning
confidence: 99%
“…For the ICDSC score, the sample size was too small and the relations between the score and LOS still need to be verified (22). Finally, the Braden Score might not be generalizable because it was developed through a single-center-study (23). A predictive risk model that is widely used in the assessment of LOS is still relatively lacking (in terms of, for example, considerations related to accuracy, specificity, and applicability), so it is important to develop a model with improved predictive ability.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, higher risk Braden scores were common in hospitalized heart failure patients but were not independent predictors of survival. Bandle et al also used the Braden score to evaluate whether it can predict outcomes including mortality, length of stay and discharge destination in a retrospective review of 642 heart failure patients 15 . After adjustment, higher Braden score was significantly associated with decreased 30‐day mortality (discharge Braden OR 0.81 [95% CI 0.66‐0.996]), decreased average LOS (admission Braden β −0.52 days [ P = .0002]) and associated with discharge to home (OR 1.66 [95% CI 1.42‐1.95]).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in different populations of hospitalized patients have shown that the BS may be associated with short-term mortality in acutely ill patients, especially with BS ≤ 15 (Bandle et al, 2017;Jentzer et al, 2019;Rothman, Solinger, Rothman, & Finlay, 2012;Sundaram et al, 2017). In the present study, we sought to examine BS as a potential marker of frailty in COVID-19 patients, defining its association with hospital mortality in this population after adjustment for other known outcome predictors.…”
Section: Introductionmentioning
confidence: 96%